Modified Thoracoplasty for Rib Hump Deformity in Scoliosis Patients: A Case-Control Study - Yuan, Hao; Wang, Minglang; Lei, Fei; Zheng, Lipeng; Chen, Zan; Feng, Daxiong (World neurosurgery, 2024)
Razorback deformity with stiff thoracic scoliosis creates a complex three-dimensional deformity. Posterior spinal fusion (PSF) and thoracoplasty can correct rib hump deformity and improve patient satisfaction. However, conventional thoracoplasty may impair pulmonary function and increase complications. We present a modified thoracoplasty (MTP) technique for addressing rib hump deformity in stiff thoracic scoliosis patients, emphasizing its clinical efficacy and safety. This study included 44 patients with stiff thoracic scoliosis and razorback deformity who underwent surgery between January 2010 and May 2021. Patients were divided into PSF + MTP (n = 27) and PSF (n = 17) groups. Surgical parameters, complications, radiographic improvements, pulmonary function, and Scoliosis Research Society-22 scores were evaluated preoperatively and at 3 months and 2 years postoperatively. There were no significant differences in baseline characteristics between the 2 groups, except for the rib hump height, which was higher in the PSF + MTP group. The PSF + MTP group showed superior correction of the thoracic curve and rib hump height compared to the PSF group, with significant improvements in self-image scores. No significant differences were observed in pulmonary function between the groups. The operative time was longer in the PSF + MTP group, but there were no significant differences in intraoperative blood loss, hospitalization costs, or major complications. Regression analysis indicated that the type of surgery, thoracic Cobb angle, and preoperative self-image scores were significant predictors of postoperative self-image scores. MTP provides enhanced correction of thoracic curve and rib hump deformity without significantly increasing pulmonary function impairment or complication rates. It also improves patients' self-image, making it a valuable addition to PSF in treating stiff thoracic scoliosis with rib hump deformity.